Thermodynamically-consistent constitutive modeling of aligned Silk fibroin sponges: Theory and application to uniaxial compression. (1st May 2018) - Panda, Debojyoti; Konar, Subhajit; Bajpai, Saumendra K.; Arockiarajan, A.
Highlights: A nonlinear viscoelastic model is developed within a thermodynamic framework. Finite strain compressive response is successfully predicted using the model. The model is applicable over a wide range of material concentrations of SF sponge. Volumetric behavior of the hydrated sponges under finite strain is also captured. Abstract: Microstructurally-aligned Silk fibroin sponges have emerged as a viable candidate for replicating the anisotropic fibrous microarchitecture that is encountered in several functional tissues in vivo . But for the material to reach its full potential in terms of its application in biomimetic soft tissue constructs or scaffolds, a complete understanding and quantification of its nonlinear viscoelastic response in the finite strain regime is needed. To address this gap from the mechanical modeling perspective, an anisotropic, nonlinear, viscoelastic model is developed within a thermodynamic framework in this study, to capture the macroscopic response of these sponges in a phenomenological manner. The rate-type constitutive equations that are developed in the process are subsequently applied for the case of uniaxial compression, and satisfactorily corroborated against the results from finite strain viscoelastic characterization experiments done on hydrated Silk fibroin sponges under uniaxial compression for different constituent material concentrations of the sponges ranging from 1 w/v % - 4 w/v %.